Procurement Monitoring and Social Accountability : Curriculum Development Program - World Bank (World Bank, Washington, DC, 2017)
The devolution of procurement responsibilities to local levels of government is increasingly occurring across South Asia. This trend is significant because increasingly localized decision-making better enables communities to hold government authorities accountable for the effectiveness of public spending, which can lead to various improved development outcomes, such as improvements in quality of service delivery; greater empowerment and understanding by end-users services supplied through public procurement processes; and improved oversight and accountability of service delivery agencies. The objective of this report is to set out an overview of the strategic approach developed by World Bank Institute (WBI) as a component of the Norwegian governance trust fund (NTF) program `procurement and service delivery: establishing effective collaboration between government and beneficiaries on monitoring procurement outcomes`. WBI received funds under the NTF to facilitate the development of context and audience-specific knowledge products by recognized practitioners and civil society organizations in South Asia as part of a broader effort to create a practical curriculum on social accountability in procurement.